Welfare of the minorities - Agwani, M.S. (1996)
"No doubt efforts have been made for the educational and economic uplift of the minorities, yet much remains to be done. What is needed now is a creditable plan of action complete with an effective machinery for its implementation and the necessary budgetary support. The recent review of the 15-Point Programme and other welfare schemes for the minorities at the PM's level is a positive sign of progress, feels the author"
Keywords: Ethnic groups - India; Minorities - India; Minority groups